2018
DOI: 10.5812/ijhls.79607
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Resource Management Learning Strategies and Academic Achievement

Abstract: Background: Learning strategies are methods that students can use to guide their learning and thinking processes. Objectives: This study aimed to explore the relationship between resource management learning strategies and academic achievement in college students. Methods: This cross-sectional descriptive study was conducted among 300 students in western Iran. Random sampling was used to select participants, and a self-reporting questionnaire was used to collect data. Data were analyzed with SPSS-21 software u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A lot of resource management strategies was also conducted. Vaezi et al (2018) found out how their strategies could predict students' time and study environment achievement. Regression analysis showed how these resource management strategies are related to their achievement.…”
Section: Motivated Learning Strategiesmentioning
confidence: 99%
“…A lot of resource management strategies was also conducted. Vaezi et al (2018) found out how their strategies could predict students' time and study environment achievement. Regression analysis showed how these resource management strategies are related to their achievement.…”
Section: Motivated Learning Strategiesmentioning
confidence: 99%